Microleakage of two types of low-shrinkage composite resins in class II cavities on primary molars - Fatemeh Pachenari; Shima Nourmohammadi; Saber Babazadeh; Sara Maleki Kambakhsh (Babol University of Medical Sciences, 2019)
Introduction: In direct aesthetic restoration, microleakage resulting from polymerization shrinkage of resin composites is still challenging. Different strategies such as maximizing the amount of inorganic filler with prepolymerized filler and different silorane matrixes have introduced to overcome this issue. The aim of this experimental study was to compare the microleakage in low-shrinkage methacrylate-based (Clear fil AP-X) and silorane-based (Filtek P90) composite resins in class II cavities on primary molar teeth. Materials & Methods: Classic class II slot cavity preparation was done on 60 healthy human primary molars. Specimens were randomly divided into two groups. For restoring the cavity in group I: methacrylate-based composite resin, and in group II: silorane-based micro-hybrid composite resin were used. The samples were thermocycled and soaked in 2% basic fuchsine dye for 24 h. They were longitudinally sectioned and observed at the gingival margins under ×10 magnification. Scores were assigned upon the amount of dye penetration. The Mann-Whitney U-test through SPSS19.0 was used for statistical analysis of data. Results: In both groups, the major of samples showed score 0 of dye penetration. The comparison of gingival margin leakage indicated no significant difference between two groups. Conclusion: Both restorative materials, irrespective of their type had microleakage. Given the comparable microleakage of silorane-based (Filtek P90) and low-shrinkage methacrylate-based (Clear fil AP-X) composite resins in Class II cavities of primary molars, the clinical efficacy of both materials seems to be similar.